"You're going to look at me differently": A qualitative study of disclosure experiences among survivors of military sexual assault. Issue 3 (26th February 2022) - Rufa, Anne K.; Carroll, Kathryn K.; Lofgreen, Ashton; Klassen, Brian; Held, Philip; Zalta, Alyson K.
Abstract: Most survivors of sexual assault who disclose their experience do so within their social network. Prior research on disclosure among individuals who experience sexual trauma has mainly focused on childhood sexual abuse, college‐aged women, or disclosure to formal sources of support (e.g., treatment providers). There is limited research on disclosure among veteran survivors of military sexual assault (MSA). The current qualitative study aimed to explore the disclosure experiences of treatment‐seeking survivors of MSA. Participants were 17 veterans ( n = 13 women, n = 4 men), aged 33–65 years, who reported experiencing MSA. During semistructured interviews, participants were asked about their experiences disclosing MSA to informal support persons (e.g., family members, partners, friends). A narrative thematic analysis identified 11 themes that emerged throughout different aspects of the disclosure, including (a) preparation and reason for disclosure (reactive or spontaneous disclosures, disclosure as an explanation/obligation), (b) expectations about the disclosure experience (no expectations, negative expectations grounded in socialized beliefs, positive expectations based on specific relationships, mismatch between experience and expectation), (c) the actual disclosure experience (negative experiences of personalization, supportive responses, share shame), and (d) military context (disclosing to another member of the military, reporting dynamics). Additional subthemes were nested within these categories. The findings indicated common experiences across participants, particularly regarding disclosure rationale. Key differences were largely influenced by contextual factors (e.g., response of the disclosure recipient). These findings hold implications for clinicians working with survivors of MSA who are preparing for and coping with the consequences of disclosure.